PHYSICAL CHARACTERISATION OF FOUR DIFFERENT COMMERCIAL DIGITAL BREAST TOMOSYNTHESIS SYSTEMS. Issue 3 (15th February 2018) - Ortenzia, O; Rossi, R; Bertolini, M; Nitrosi, A; Ghetti, C
Abstract: The aim of this article was to characterise the performance of four different digital breast tomosynthesis (DBT) systems in terms of dose and image quality parameters. One of them, GE Pristina, has never been tested before. Average glandular doses were measured both in DBT and 2D full field digital mammography mode. Several phantoms were employed to perform signal difference to noise ratio, slice sensitivity profile, slice to slice incrementation, chest wall offset, z -axis geometry, artefact spread function, low contrast detectability, contrast detail evaluations, image uniformity and in-plane MTF in chest wall-nipple and in tube-travel directions. There are many differences in DBT systems explored: the angular range, detector type, reconstruction algorithms, and the presence or not of the grid. Even if it is not simple to calculate a global figure of merit, the analysis of all the collected data can be useful in a contest of a quality assurance program to define a set of values that could be used as benchmarks.